2019
DOI: 10.1101/619676
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping Transcription Factor Networks By Comparing Tf Binding Locations To Tf Perturbation Responses

Abstract: 26 Background: A transcription-factor (TF) network map indicates the direct, functional targets of 27 each TF --the genes it regulates by binding to their cis-regulatory DNA. Data on the genomic 28 binding locations of each TF and the transcriptional responses to perturbations of its activity, 29 such as overexpressing it, could support TF network mapping. Systematic data sets of both 30 types exist for yeast and for human K562 and HEK293 cells. 31 Results: In previous data, most TF binding sites appear to be … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…However, it is important to note that these two evidence sources rarely converge on a common set of target genes. Despite being widely used as the gold standard, even the bound and differentially expressed genes may not be the validated functional targets (Kang et al, 2020).…”
Section: Innovative Approaches For Aggregating Tfbinding and Gene Exp...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to note that these two evidence sources rarely converge on a common set of target genes. Despite being widely used as the gold standard, even the bound and differentially expressed genes may not be the validated functional targets (Kang et al, 2020).…”
Section: Innovative Approaches For Aggregating Tfbinding and Gene Exp...mentioning
confidence: 99%
“…This method improves the accuracy of identifying direct functional targets by combining data from TF binding sites and TF perturbation responses. The DTO method enhances the convergence of two data types by optimizing the significance thresholds for binding and responsive data (Kang et al, 2020). Morin and colleagues built upon two existing strategies (Tang et al, 2011;Wang et al, 2013) to create a framework to identify and rank TF-target interactions, and identified potential orthologous interactions between humans and mice.…”
Section: Innovative Approaches For Aggregating Tfbinding and Gene Exp...mentioning
confidence: 99%
“…Alternatively, genetic perturbations with expression or growth-rate as readouts can be used to group functionally similar genes and processes [8,9] . Gene expression profiling of deletion mutants (i.e., asymptotic readouts of a perturbation) can help identify co-regulated genes, though without dynamics there is limited potential for determining direct regulatory relationships because how information propagates from the deletion to each differentially expressed gene is not observed [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Deciphering the complicated process of gene regulation was one of the key research objectives during the past several decades [8][9][10] . Due to the synchronized work of multiple systems controlling mRNA synthesis and decay 11,12 , the average steady state levels of individual mRNAs may vary from less than one copy per cell to several hundreds per cell across different environmental conditions 13 .…”
mentioning
confidence: 99%